An asymmetric end-capping strategy enables a new non-fullerene acceptor for organic solar cells with efficiency over 10%. Issue 48 (12th May 2020) - Duan, Tainan; Hou, Licheng; Fu, Jiehao; Kan, Zhipeng; Yang, Qianguang; Chen, Qianqian; Zhong, Cheng; Xiao, Zeyun; Yu, Donghong; Lu, Shirong
Abstract : A new asymmetric non-fullerene acceptor (IDTBF ) that features two distinct terminal groups was designed and synthesized. The device based on polymer donor PM6 and IDTBF exhibits a promising PCE of 10.43%. Abstract : Two different terminal groups, rhodanine-flanked benzo[ c ][1, 2, 5]thiadiazole (BR) and 2-(5, 6-difluoro-3-oxo-2, 3-dihydro-1 H -inden-1-ylidene)malononitrile (IM2F), were connected to an indaceno[1, 2- b :5, 6- b ′]dithiophene (IDT) core to construct a new non-fullerene acceptor (IDTBF ). Solar cells based on this acceptor exhibited promising photovoltaic performances with a power conversion efficiency (PCE) of up to 10.43%.